2009
DOI: 10.2478/v10043-009-0031-6
|View full text |Cite
|
Sign up to set email alerts
|

Diet of Otters in Fish Farms in Lithuania

Abstract: The diet of the otter (Lutra lutra) was studied in three fish farms and a state hatchery in Lithuania in 2006-2007 by spraints analysis. The relative frequency of occurrence (O) and biomass consumed (B) were estimated. Fish made the bulk of the otter diet and was the only important food item (68.0-96.7% O, 87.5-99.8% B). Other items (mammals, birds, amphibians, crustacean, insects, and molluscs) generally comprised a minor part of the diet (3.3-32.0% O, 0.2-12.5% B) with significantly higher consumption in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This might be an effect of the high percentage of fishponds in the standing waterbodies studied (50% of standing water study sites were fishponds). Fish in fishponds are both abundant and easy to prey on (Lanszki & Kormendi , Kloskowski , Lanszki & Molnar , Baltrūnaitė ). Thus, the energetic importance of non‐fish prey is small, as well as their occurrence in faeces.…”
Section: Discussionmentioning
confidence: 99%
“…This might be an effect of the high percentage of fishponds in the standing waterbodies studied (50% of standing water study sites were fishponds). Fish in fishponds are both abundant and easy to prey on (Lanszki & Kormendi , Kloskowski , Lanszki & Molnar , Baltrūnaitė ). Thus, the energetic importance of non‐fish prey is small, as well as their occurrence in faeces.…”
Section: Discussionmentioning
confidence: 99%
“…In fish farms in Eastern Europe, otter biomass consumption can be composed almost entirely of carp (e.g. Kortan et al 2007;Baltrūnaitė 2009). Artificially stocked carp fisheries are common in the study region (Crawford 2010), but wild common carp were also occasionally detected at the study sites during EA electrofishing surveys.…”
Section: Evidence For Prey Selection By Ottersmentioning
confidence: 99%
“…Emmerson and Philip (2004) reported that the diet of African clawless otter varies with site due to the wide distribution throughout Sub-Saharan Africa. Studies by Baltrunaite (2009) in Lithuania also noted that changes in the diet of otters are related to different habitat. Rowe-Rowe (1977) and Rowe-Rowe and Somers (1998) also reported that diet of the African clawless otter varies depending on locality, season and prey availability.…”
Section: Discussionmentioning
confidence: 97%